Transperitoneal Laparoscopic Pyelopyelostomy for Retrocaval Ureter without Excision of the Retrocaval Segment: Experience on Three Cases - Y. El Harrech; O. Ghoundale; E. H. Kasmaoui; D. Touiti (Advances in Urology)
Introduction. Retrocaval ureter is a rare congenital anomaly. Open surgery was the classic treatment for this condition. Laparoscopy is currently an admitted procedure to treat many urological diseases. The objective of our study is to present our experience and discuss the safety and the feasibility of transperitoneal laparoscopic pyelopyelostomy for treatment of retrocaval ureter (RCU). Materials and Methods. Three symptomatic patients underwent laparoscopic repair for RCU in our department. The diagnosis was suspected on the computed tomography scan (CT) and confirmed on ascending pyelography. After placement of a JJ stent, and, using the transperitoneal approach, the retro peritoneum was exposed; the ureter was identified in both sides of the vena cava. The retrocaval segment was entirely mobilized and pulled from behind of the vena cava after section of renal pelvis. A pyelopyelostomy was done in a normal anatomic position. Results. All operations were achieved laparoscopically without conversion to open surgery. The mean operative time was 140 minutes (110–190). No intraoperative complication occurred. Blood loss was less than 50 mL in all patients. The mean hospital stay was 5 days (4–6 days). All patients were symptom-free after surgery and had reduction of hydronephrosis in control imagery. Conclusion. Laparoscopy seems safe, feasible, and reproducible in managing retrocaval ureter.